IR813-Induced Photothermal Therapy: Leveraging Immunogenic Cell Death for Cancer Treatment - Guangwei Jiang; Rong Huang; Min Qian; Wenjuan Hu; Rongqin Huang (Pharmaceutics)
Background: Photothermal therapy has the potential to enhance the precision and safety of oncological treatments. However, applicable photothermal agents associated with its photothermal activated immunogenic cell death remain exploiting. Methods: This study evaluates the effectiveness of IR813, a photothermal agent, combined with near-infrared (NIR) light for cancer treatment. In vitro, 4T1 cancer cells were treated with IR813 (5 μg/mL) and exposed to NIR irradiation (1 W/cm2) for 5 min. In vivo, after the tumor-bearing mice administered with IR813 (1 mg/kg) and exposed to NIR irradiation (1 W/cm2) for 10 min, the tumor volume, survival and immune activation were evaluated. Results: IR813 significantly increased the cytotoxicity of 4T1 cancer cells following near-infrared irradiation, resulting in the release of damage-associated molecular patterns and immunogenic cell death. Specifically, the cell viability was reduced to 5% compared to the control group. In vivo, irradiating the accumulation of IR813 at the tumor site had the potential to mediate substantial photothermal tumor suppression, improved mouse survival, and reduced metastasis, with minimal adverse reactions. Furthermore, the immune responses stimulated by IR813-induced photothermal therapy were evidenced by increased mature dendritic cell and cytotoxic T lymphocyte counts and a decrease in regulatory T cells in the spleen, tumor, and lymph nodes. Conclusions: These findings suggest that IR813-induced photothermal therapy is a promising approach for enhancing immunotherapy, directly inhibiting tumors while boosting systemic anti-cancer immunity.